2012
DOI: 10.1038/jid.2011.256
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine Receptors Are Expressed in Epidermal Keratinocytes and Associated with Keratinocyte Differentiation and Epidermal Permeability Barrier Homeostasis

Abstract: Ryanodine receptors (RyRs) have an important role as calcium channels in the regulation of intracellular calcium levels in the nervous system and muscle. In the present study, we investigated the expression of RyR in human epidermis. Immunohistochemical studies and reverse transcription-PCR indicated the expression of RyR type 1, 2, and 3 proteins in epidermal keratinocytes. The expression level of each RyR subtype was higher in differentiating keratinocytes than in proliferative cells. We also demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…This Ca 2+ gradient depends on a competent epidermal barrier (Mauro et al, 1998; Menon and Elias, 1991; Menon et al, 1994), which in turn is formed by keratinocyte Ca 2+ uptake, release, and influx (Feingold and Denda, 2012; Hu et al, 2000; Man et al, 1997). Studies from our group (Celli et al, 2010) and others (Adams et al, 2012; Cornelissen et al, 2007; Denda et al, 2012) have identified intracellular, rather than extracellular, calcium stores as the main components of the epidermal calcium gradient, and shown that ER Ca 2+ release alone can control barrier repair processes (Celli et al, 2011). …”
Section: Introductionmentioning
confidence: 98%
“…This Ca 2+ gradient depends on a competent epidermal barrier (Mauro et al, 1998; Menon and Elias, 1991; Menon et al, 1994), which in turn is formed by keratinocyte Ca 2+ uptake, release, and influx (Feingold and Denda, 2012; Hu et al, 2000; Man et al, 1997). Studies from our group (Celli et al, 2010) and others (Adams et al, 2012; Cornelissen et al, 2007; Denda et al, 2012) have identified intracellular, rather than extracellular, calcium stores as the main components of the epidermal calcium gradient, and shown that ER Ca 2+ release alone can control barrier repair processes (Celli et al, 2011). …”
Section: Introductionmentioning
confidence: 98%
“…As epidermal keratinocytes express ryanodine receptors (24), the endogenous mechanism of OT secretion from epidermal keratinocytes might be similar to that of hypothalamus. OT release by ATPcS was blocked by the removal of Ca…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Orai1 results in inhibited directional migration of keratinocytes [95]. Moreover, expression of RyRs in human keratinocytes has been linked to keratinocyte differentiation and epidermal barrier homeostasis [96]. Application of a RyR agonist or antagonist delays or enhances skin barrier recovery respectively [96].…”
Section: Calcium Signaling In Muscle Regenerationmentioning
confidence: 99%
“…Moreover, expression of RyRs in human keratinocytes has been linked to keratinocyte differentiation and epidermal barrier homeostasis [96]. Application of a RyR agonist or antagonist delays or enhances skin barrier recovery respectively [96]. Further studies will help determine whether the importance of Ca 2+ activity in regeneration is universal and will identify the particular Ca 2+ dynamics that facilitate regeneration in different tissues.…”
Section: Calcium Signaling In Muscle Regenerationmentioning
confidence: 99%